Influence of Low-Level Laser Modification and Adhesive Application Mode on the Bonding Efficiency of Universal Adhesives to Er:YAG Laser-Ablated Dentin - Elsahn, Nesrine Ali; El-Damanhoury, Hatem M.; Elkassas, Dina W (Journal of Lasers in Medical Sciences, 2021)
Introduction: Erbium laser ablation as a method of tooth preparation and conditioning has shown promising results. Although previous studies have adopted various combinations of different laser parameters and several dentin adhesive systems, very few have investigated combining high-level and low-level Er: YAG lasers with Universal adhesives. This study aimed to assess the impact of using low-energy irradiation on the surface micro-topography and shear bond strength (SBS) of universal adhesive (UA) to the erbium:yttrium-aluminum-garnet (Er: YAG) laser-ablated dentin substrate, bonded in etch-and-rinse or self-etch adhesive mode. Methods: Eighty-seven extracted molars were sectioned to expose flat occlusal dentin surface; 60 teeth were divided equally into three groups according to the surface treatment; bur-cutting (B), Er: YAG high-energy laser cutting, or L1 followed by low-energy laser modification. Then each group was equally divided into two groups (n=10) according to the mode of application of the universal adhesive; either etch-and-rinse (ER) or self-etching (SE). The samples were subjected to thermocycling (5000 cycles between 5°C and 55°C), and SBS was tested. Two-way ANOVA and Tukey post hoc test was used to analyze the results. The remaining 27 samples were used to investigate the effect of the treatment on the topography of the treated dentin surfaces using a scanning electron microscope (SEM). Results: B/SE recorded the highest SBS (25.48 ± 2.6 MPa) followed by B/ER and L1/L2/SE (22.94 ± 4.1 MPa) and with no statistically significant difference between these groups (P >0.05). The lowest SBS results (P<0.05) were recorded for L1/SE (12.22 ± 3 MPa). No statistical differences were found between the SBS of L1/L2/ER and L1/ER groups or between the SBS of L1/L2/ER and L1/L2/SE groups. Conclusion: A subsequent treatment of the Er: YAG laser-ablated dentin with low-energy laser modification mode (LMM) enhances the SBS of the tested UA when applied in SE mode. DOI:10.34172/jlms.2021.07